Експериментальна реконструкція давньоруського гончарного горну (за матеріалами ремісничого посаду Вишгорода) - Оленич, А.М.; Бібіков, Д.В.; Івакін, В.Г.; Зоценко, І.В. (Археологія і давня історія України, 2017)
Статтю присвячено одному з напрямів у сучасній експериментальній археології — історичній реконструкції давньоруського гончарства. На базі Олевської археологічної експедиції авторами здійснено спробу відтворення копії давньоруського гончарного горну. Вказаний комплекс було досліджено у ході археологічних досліджень гончарного ремісничого посаду давнього Вишгорода у 2013 р. Було відтворено основні етапи зведення випалювального пристрою, перевірено ефективність та простоту його експлуатації. Статья посвящена одному из направлений современной экспериментальной археологии — исторической реконструкции древнерусского гончарства. На базе Олевской археологической экспедиции авторами была предпринята попытка воспроизведения копии древнерусского гончарного горна. Указанный комплекс был исследован в ходе археологических исследований раскопок гончарного ремесленного посада древнего Вышгорода в 2013 г. The article is dedicated to one of the modern trends in experimental archeology — historical reconstruction of ancient pottery. Based on Olevsk archaeological expedition authors made attempt to reconstruct up old rus pottery kiln. The last one was investigated during excavations on pottery trading quarter of Old Rus Vyshgorod in 2013. The article briefly served the history of archaeological study of pottery quarters of the town. Analyzed variations in sizes and designs Vyshgorod pottery kiln of 11 century. It checked the main stages of the construction unit kilns for ceramics. Checked viability design, ease of construction and maintenance, efficiency and ease of operation. Proved and tested a significant number of observations and conjectures about the individual structural elements, materials and methods of forming the body of the furnace, construction feasibility in the trench, conditioning design. Checked feasibility removable canopy over the kiln.